2023
DOI: 10.17305/bb.2022.8050
|View full text |Cite
|
Sign up to set email alerts
|

OVID-19 in the Federation of Bosnia and Herzegovina: Strengthening the public health surveillance using a web-based system to inform public health response, March 2020 - March 2022

Abstract: In response to the significant public health threat caused by coronavirus disease (COVID-19), real-time surveillance, containment, and mitigation measures were implemented in the Federation of Bosnia and Herzegovina (FBiH). Our objective was to describe the surveillance methodology, response measures, and epidemiology of COVID-19 cases in FBiH from March 2020 to March 2022. The surveillance system implemented across FBiH enabled health authorities and the population to monitor the development of the epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Pijls et al, in their meta-analysis, found that men were at a higher risk of contracting SARS-CoV-2 infection [30], which was also confirmed by the study in a highly vaccinated population of HCWs during the first year of the vaccination campaign (before Omicron) [13]. However, other studies have demonstrated a higher percentage of female patients in the population of COVID-19 patients [14,15,[31][32][33][34]. Globally, a large proportion of the health and social care workforce is represented by women, exposing them to a higher risk for morbidity, both at work and at home, when caring for sick family members [35,36].…”
Section: Discussionmentioning
confidence: 72%
“…Pijls et al, in their meta-analysis, found that men were at a higher risk of contracting SARS-CoV-2 infection [30], which was also confirmed by the study in a highly vaccinated population of HCWs during the first year of the vaccination campaign (before Omicron) [13]. However, other studies have demonstrated a higher percentage of female patients in the population of COVID-19 patients [14,15,[31][32][33][34]. Globally, a large proportion of the health and social care workforce is represented by women, exposing them to a higher risk for morbidity, both at work and at home, when caring for sick family members [35,36].…”
Section: Discussionmentioning
confidence: 72%
“…It is important to note that one of the greatest European outbreak caused by L. monocytogenes The media attention for these outbreaks may indirectly raise awareness among consumers and make them more precaution. Note that Turkey and India do not have an active surveillance system covering the incidence of listeriosis, and in Bosnia no cases of listeriosis have been previously reported (Musa et al 2020).…”
Section: Attitudes Towards Chilled Rte Foodsmentioning
confidence: 99%
“…By May 16, 2020, the number of confirmed COVID-19 cases had surged to 2,236, prompting the government to implement widespread restrictive measures, including movement restrictions, closure of public institutions, cafes, bars, and restaurants, as well as restrictions in public spaces and airports 6 . By March 31, 2022, B&H had documented 249,495 COVID-19 cas-es and 8,845 COVID-19-associated deaths 7 . Nearly a year later, a combination of low vaccine acceptance rates, limited health care resources and fatigued healthcare workers, created a challenging environment for B&H to effectively manage the ongoing COVID-19 pandemic [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%